Enhancing Global Halal Tourism in Indonesia: The Mediating Role of Religious Commitment - Manggarani, Cynthia Ayu; Patiro, Shine Pintor Siolemba (Hasanuddin Economics and Business Review, 2025)
Halal tourism has become a significant global trend, forming a distinct market segment. Despite promotional efforts by governments and local communities, visitor numbers to halal destinations remain inconsistent. This study explores religious commitment as a moderating variable within the Theory of Trying framework, a model that effectively explains high-involvement consumer behaviors like tourism. While the Theory of Trying is less commonly applied in consumer behavior research compared to the Theory of Planned Behavior, it offers valuable insights into understanding tourist behavior. The study specifically examines whether religious commitment strengthens the intention of tourists to engage in halal tourism in Aceh. Employing a quantitative approach and Structural Equation Modeling (SEM) for data analysis, the findings reveal that attitudes toward success, failure, the process, and subjective norms significantly influence consumption behavior, with attitudes toward the process showing the strongest effect, highlighting the importance of psychological factors in shaping consumer intentions.